Utilización de suplemento energético para nutrición animal en cerdos, Línea Comercial, en la etapa de inicio (07-28 días) - Pablo Avalos, Juan Gabriel (2020)
The present investigation was carried out with the objective of evaluating the effect of the use of an energy supplement in the starter diet for commercial line piglets; Located in the Chao district; also, identify the piglets that respond more efficiently to the use of the energy supplement; Calculate the production and productivity of commercial line piglets at the start stage (07-28 days) per treatment, the research will be a Completely Random Design (DCA), data that were analyzed using Excel 2019 Software. 60 piglets were evaluated from the 7 days of age of which were divided into three treatments: T1 (4kg of energy supplement) T2 (3.5 of energy supplement) and T3 (Witness) in order to evaluate the following parameters initial live weight, final live weight, gain of weight, food consumption, food conversion, morbidity, mortality and productivity. The results obtained show a significant difference (P˂0.05) for the final weight gain in the three treatments. Numerical differences were found in food conversion, for T1 (0.54) compared to the other treatments T2 (0.57) and T3 (0.79). It is concluded that the use of energy supplement for animal nutrition in pigs, commercial line, in the beginning stage (07- 28 days) generates greater productivity than conventional feeding.